The role of cyclone activity in snow accumulation on Arctic sea ice - M. A. Webster (Nature Portfolio, 2019)
Snow cover can affect the Arctic sea-ice system in different ways. Here authors study the relationship between cyclone activity and the seasonal build-up of snow on Arctic sea ice at a multi-decadal and basin-wide scale and find that 44% of the variability in monthly snow accumulation was controlled by cyclone snowfall and 29% by sea-ice freeze-up with strong spatio-temporal differences.